Pelatihan Manajemen Sederhana Keuangan Keluarga Di Desa Pelawi Selatan - Edi Sofyan; Zulkifli Siregar; Fauzi Fauzi; Adrian Maulana Batubara; Fitri Makhfirah; Mutiara Rizky Ritonga (Universitas Islam Sumatear Utara, 2023)
Community Service Training on Family Financial Planning and Simple Bookkeeping for Housewives has the aim of training family financial planning and simple bookkeeping for housewives, especially for women in Pelawi Selatan Village, Babalan District, Langkat Regency. Based on the initial survey of 10 respondents, it is known that out of 10 participants, mothers and housewives have not carried out family financial planning properly. The record keeping is still very limited, that is, it only records people's debts. The service method uses counseling and qualitative analysis. The results of the service, after the pre-test and post-test were carried out from 10 counseling participants, all of the 10 participants had understood family financial planning and simple bookkeeping for housewives. So, housewives can do family financial planning and can make simple bookkeeping for housewives and can record family finances well.